Implementing the Merdeka Curriculum in Vocational ELT: Challenges, Enablers, and Implications for Students’ Employability - Yayu Anggraini H. Katili; Rasuna Talib (FOSTER: Journal of English Language Teaching, 2026)
Despite growing attention to curriculum reform in Indonesia, limited empirical research has examined the implementation of the Merdeka Curriculum in English language teaching in tourism vocational schools in relation to students’ employability. This study explores the implementation of the Merdeka Curriculum in ELT at Bubohu Tourism Vocational School in Gorontalo. This research focuses on supporting factors, challenges and implications for students’ work readiness. This research used a qualitative case study design involving three English teachers and five students. Data were collected through classroom observations, semi-structured interviews and document analysis, then analyzed thematically. The findings show that curriculum documents were complete and aligned with student-centered learning principles. However, classroom practices remained mostly teacher-directed and focused on theoretical instruction. Supporting factors included teachers’ commitment and students’ enthusiasm for practice-based learning, while limited professional training and inadequate facilities hindered implementation. In terms of employability, students demonstrated progress in technical service skills, work attitudes, and self-confidence through practical activities, although communicative and ESP-based learning opportunities remained limited. This study highlights the gap between curriculum expectations and classroom practices and emphasizes the need for ESP-oriented teaching to support students’ employability.